Penerapan Strategi Belajar Tuntas (Materi Learning) dalam Meningkatkan Hasil Belajar Siswa Kelas II SD Negeri 1 Praya - Juaeriah, Juaeriah (YASIN, 2022)
This study aims to describe the application of complete learning strategies (Meteri Learning) in improving student learning outcomes for class II SDN 1 Paraya Central Lombok Regency in the academic year 2021/2022 with a population of 24 people, sampling by means of saturated samples, i.e. all populations are taken as samples, because the population is less than 100 the research is a demonstration research that directly demonstrates the process in front of the class with the guidance of teachers and other teachers as research colleagues in conducting research, and in collecting data in this study the authors used interviews, documentation, observations and tests in order to obtain results in the form of qualitative data in the form of an elaboration to determine the extent to which the implementation of complete learning strategies (Meteri Learning) in improving the learning outcomes of second grade students at SDN 1 Paraya, Central Lombok Regency, in the 2021/2022 academic year. The results of this study are: there is an effect of the Implementation of Complete Learning Strategies (Meteri Learning) in Improving the Learning Outcomes of Class II Students of SDN 1 Praya. So in this case it can be concluded that the use of the teacher's demonstration method greatly influences students' learning abilities which in quantitative form obtained from educative interactions are: initial value = 5.04 and cycle I value of 6.87 and grade = 7.66. So that the use of the demonstration method can affect students' learning abilities in increasing their creativity and effectiveness in learning together both at home and especially at school and under the guidance of the teacher's mother and father.